Pengaruh Pengalaman Kerja, Pengawasan, dan Disiplin Kerja Terhadap Kinerja Pegawai - Muhammad Ali Ridho; Wulan Apriliani (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
This study aims to examine the effect of work experience, supervision, and work discipline on employee performance at the Dasuk Health Center, Sumenep Regency. Employee performance is one of the important factors in improving the effectiveness of public health services. This study used a quantitative method with a survey approach, involving 100 employees as a sample taken randomly. Data were collected through questionnaires measuring the variables of work experience, supervision, and work discipline as well as employee performance. The results of the analysis showed that work experience, supervision, and work discipline have a significant influence on employee performance. This finding indicates that increasing work experience, supervisory effectiveness, and implementing good work discipline can improve employee performance at the Dasuk Health Center. This study provides recommendations for Puskesmas managers in designing more effective human resource development strategies to improve health service performance.